Bee pollen supplementation in diets for rabbit does and growing rabbits - doi: 10.4025/actascianimsci.v35i4.18950 - Dias, Daisa Mirelle Borges; Oliveira, Maria Cristina de; Silva, Diones Montes da; Bonifácio, Nadielli Pereira; Claro, Daniel da Cunha; Marchesin, Wilson Aparecido (Acta Scientiarum. Animal Sciences, 2013)
It was evaluated the effects of bee pollen (BP) on the doe and kits productivity and on the carcass and organs of the rabbits. Twenty White New Zealand does and their kits were used in a randomized block design, with four treatments and five blocks, in a factorial arrangement 2 x 2 with two supplementation levels for the doe and for the kits after the weaning. BP supplementation for the does did not influence (p > 0.05) the doe and kit productivity during the lactation, except by the kits survival rate (p < 0.003), the total (p < 0.002) and daily (p < 0.001) milk production that increased in supplemented doe. BP supplementation for the doe and/or kits did not affect (p > 0.05) the rabbit performance from the weaning until the slaughter age, the slaughter weight, carcass characteristics, except by the spleen and small intestine weights, higher in supplemented rabbits. It was not recommended that BP supplementation for does and/or rabbits for not improving the rabbit productive performance